Marketing Communication of Grand Hatika Hotel in Increasing the Number of Visitors on Belitung Island - Lexianingrum, Siti Rahayu Pratami; Mandaria, Vina; Taqwa, Dwi Muhammad (INFOKUM, 2022)
Hotels in Belitung have problems in marketing in this study aiming to find out how the Marketing Communication of Grand Hatika Hotels in Increasing the Number of Enders on Belitung Island. By using a qualitative research method with a descriptive approach where research describing the object under study based on the facts in the field, using informants as sources of data, the data presented using primary data and secondary data through interviews, observation, documentation relating to research. The results of this research indicate that the Grand Hatika hotel did some marketing planning in increasing the number of visitors, namely using 4P’s model (product, price, place, promotion) and combined with the promotion mix (Advertising, sales promotion, direct marketing, public relations). In the planning process to increase the number of visitors, it can conclude that was quite successful and can be role model for other belitung, it can be prov from the increasing occupancy rate of in this hotel per year.